Improvisations on a Missing String - Yārid, Nāzik Sābā (Book collections on Project MUSE., 1997)
As she awaits an operation in hospital in Beirut, Saada Rayyis, a teacher of Arabic literature, ponders the meaning of her Christian Arab heritage. An examination of biculturalism.